Advances in the treatment of newly diagnosed glioblastoma. Issue 1 (December 2015) - Theeler, Brett; Gilbert, Mark
Abstract Glioblastoma is a refractory malignancy with limited treatment options at tumor recurrence. Only a small proportion of patients survive 2 years or longer with the current standard of care. Gene expression profiling can segregate newly diagnosed patients into groups with different prognoses, and these biomarkers are being incorporated into a new generation of personalized clinical trials. Using the experience from recently completed large scale, multi-faceted, randomized glioblastoma clinical trials, a new clinical trial paradigm is being established to move promising therapies forward into the newly diagnosed treatment setting. Upcoming trials using the immune check-point inhibitors are an example of this changing paradigm and these and other immunotherapies have potential as promising new treatment modalities for newly diagnosed GB patients.